Nutritional composition and thai consumer buying behavior of dead fertilized and incubated chicken eggs in the northeastern region of Thailand - Lokaewnanee, Kanda; Chayboonkrong, Anural; Taengtanglam, Thitaya; Trithilen, Unchan; Khumpeerawat, Panuwat; Plaengkaew, Suppasit; Sukprasert, Channarong (Journal of Advanced Veterinary Research, 2025)
This study examined consumer purchasing behavior toward dead fertilized and incubated chicken eggs (balut) in the upper northeastern region of Thailand, alongside their nutritional composition. Two trials were conducted. In Trial 1, data were collected from 400 respondents through a structured questionnaire to assess factors influencing purchase decisions. Results indicated a stronger preference for dead fertilized egg over incubated eggs. Participants favored consuming the yolk and white separately in dead fertilized eggs, citing superior taste, texture, and overalleating experience. Trial 2 analyzed the nutrient profiles of different egg types. Whole boiled chicken eggs contained the highest moisture content (P<0.05), dead fertilized eggs showed the greatest fat levels (P<0.05), and incubated eggs exhibited the highest protein and vitamin A content (P<0.05). Overall, odor was identified as the primary factor influencing consumer choice, with dead fertilized eggs generally preferred. Nutritionally, dead fertilized eggs offer notable fatcontent, while incubated eggs provide high protein and vitamin A, highlighting their for value-added egg product develpoment.